Künstliche Intelligenz: Wo stehen wir in Deutschland? - Volker Brühl (Wirtschaftsdienst, 2023)
– Artificial Intelligence (AI) is widely regarded as a technology which will impact the future competitiveness of the Germaneconomy. Looking at the research productivity of German scientists and universities in AI, we find that Germany definitively belongs tothe top performers in AI research globally, although the United States and China are somewhat ahead. This is not surprising taking intoaccount the sheer size of their talent pools. Furthermore, the majority of promising AI startups are based in the United States, while Ger-many is clearly underrepresented in the group of excellent AI startups given Germany's excellence in AI research. Hence, it is obviouslymore challenging for Germany to translate research excellence into successful entrepreneurship.
Keywords: O30; O40; 330; Künstliche Intelligenz; Forschung; Deutschland; Künstliche Intelligenz; Forschung; Deutschland